Key Factors Influencing Women’s Economic Empowerment in Rural Bangladesh: Insights and Implications for Development Policy - Rahman, Ashiqur; Ahmed, Md Tuhin; Bintay Masud, Maimuna; Jahan, Nourush; Sadekin, Md Nazmus (South Asian Journal of Social Sciences and Humanities, 2025)
Purpose: The primary objective of this study, with some specific objectives also, is to investigate the factors associated with enhancing women’s economic empowerment in rural Bangladesh. Methods: Using both quantitative and qualitative approaches, a Women’s Empowerment Index was constructed from primary data collected through surveys and interviews. Regression analysis identified key determinants of empowerment, while the logit model examined factors influencing female labor force participation, suitable for the binary dependent variable. The Ordinary Least Squares (OLS) method analyzed earnings determinants for female workers. Findings: Age, presence of children, status as heads of households, occupation, education and access to information and social media contribute significantly to economic empowerment. Policy implications: The government should prioritize expanding education access, especially for rural women, and develop vocational training programs aligned with local economic opportunities. Initiatives to improve digital literacy and provide financial and market access are crucial for fostering entrepreneurship and formal job sector participation. Policies promoting work-life balance, affordable childcare, and gender equality in employment must be implemented alongside measures to support women’s property rights, ICT access, and decision-making participation. Multi-sectoral collaborations and community awareness programs are needed to address gender stereotypes and ensure holistic empowerment. Originality of the study: By employing the most recent data set and cutting-edge methodology, the present research adds to the body of available research by revealing the factors that pose a huge impact on rural women’s economic empowerment.